Implementasi Program Tahfiz dalam Meningkatkan Hasil Belajar Siswa pada Pelajaran Pendidikan Agama Islam - Ritonga, Amir Saypuddin; Nasution, Abdul Fattah (Fitrah: Journal of Islamic Education, 2023)
The lack of student competence in learning the Qur'an is consistent with the lack of student learning outcomes. One of the efforts that is commonly used to overcome this problem is implementing the tahfiz Qur'an program. The program not only increases religiosity and character, but also improves learning outcomes. In this regard, this study aims to analyze the implementation of the tahfiz program in improving student learning outcomes in Islamic religious education lessons. SDIT Tahfizil Qur'an Islamic Center became the research location because it is indeed the basis for the tahfiz educational institution. The research method used is descriptive qualitative, with data collection techniques of observation, interviews and documentation studies. The primary data source is the homeroom teacher for class II, while the secondary sources are from documents of learning tools and relevant literature. The results of the study explained that the process of tahfiz Qur'an was carried out using the Murajaah method and the talqin method. In the implementation there are supporting factors namely, parents participating in helping murajaah at home, and inhibiting factors namely some students are not yet able and accustomed to reading the Qur'an. The research implications show that the success of the tahfiz program is influenced by the collaboration of parents and educators in maintaining memorization and making it easier for children to implement the content of verses in everyday life.